Visionary Leadership and Its Impact on School Culture: An Organizational Analysis - Sahoo, Divya Ratna; Ragendran, Raghavi (Journal of Educational Research and Policies, 2026)
Leading educational organizations to succeed requires visionary leadership principles as the most necessary factor. This study sought to determine the impact of visionary leadership on the school culture of Villanueva North District in the Division of Misamis Oriental, School Year 2024-2025. This study used correlational and causal research designs to determine the relationship between visionary leadership and school culture. The respondents for this study were one hundred thirty-one (131) public elementary and secondary teachers. The study utilized a purposive sampling technique to identify the teacher-respondents. The researcher employed a researcher- made questionnaire to assess visionary leadership and school culture. Statistical tools used to answer the problems of the study included Weighted Mean, Standard Deviation, Pearson Product-Moment Correlation Coefficient, and Multiple Linear Regression Analysis. The findings revealed a Very Positive Response level in visionary leadership as perceived by the teachers; communication has a significant effect on visionary leadership and is also the best predictor of visionary leadership and school culture. It can be concluded that school heads have a visionary leadership style. It can be recommended that school heads continue to employ the visionary leadership style. Likewise, they have to communicate with their stakeholders and teachers. School heads have to support and recognize the teachers’ ability to adapt to changes and face challenges positively.